2008
DOI: 10.1002/eji.200838269
|View full text |Cite
|
Sign up to set email alerts
|

Site‐directed mutagenesis of the chemokine receptor CXCR6 suggests a novel paradigm for interactions with the ligand CXCL16

Abstract: Chemokine receptor CXCR6 mediates the chemotaxis and adhesion of leukocytes to soluble and membrane-anchored forms of CXCL16, and is an HIV-1 co-receptor. Here, we describe the effects of mutation of acidic extracellular CXCR6 residues on receptor function. Although most CXCR6 mutants examined were expressed at levels similar to wild-type (WT) CXCR6, an N-terminal E3Q mutant was poorly expressed, which may explain previously reported protective effects of a similar single nucleotide polymorphism, with respect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 41 publications
(60 reference statements)
2
25
0
Order By: Relevance
“…Petit et al demonstrated that a point mutation of the CXCL16 receptor CXCR6 (Glu274Gln) abrogated binding of soluble (chemokine domain) CXCL16 but had no effect on adhesion mediated by full-length membrane-bound CXCL16. 40 The authors suggest that the mucin stalk in the full-length molecule causes the chemokine domain to adopt a different conformation compared with soluble chemokine domain CXCL16. These 2 forms may then stabilize different receptor conformations that induce different functional effects on cells expressing the CXCR6 receptor.…”
Section: Shed Versus Membrane-bound Fractalkinementioning
confidence: 99%
“…Petit et al demonstrated that a point mutation of the CXCL16 receptor CXCR6 (Glu274Gln) abrogated binding of soluble (chemokine domain) CXCL16 but had no effect on adhesion mediated by full-length membrane-bound CXCL16. 40 The authors suggest that the mucin stalk in the full-length molecule causes the chemokine domain to adopt a different conformation compared with soluble chemokine domain CXCL16. These 2 forms may then stabilize different receptor conformations that induce different functional effects on cells expressing the CXCR6 receptor.…”
Section: Shed Versus Membrane-bound Fractalkinementioning
confidence: 99%
“…16 HEK293T cells were transiently transfected by calcium phosphate precipitation. For a 24-well plate format, 9ϫ10 4 cells were seeded in 200 L, 1 day before transfection, and the medium was changed 3 hours before transfection.…”
Section: Cell Culturementioning
confidence: 99%
“…16 Expression of CXCL16 on HEK293T cells was detected using biotinylated anti-human CXCL16 (R&D Systems) and streptavidin fluorescein isothiocyanate (Serotec Ltd, Oxford, United Kingdom) with goat IgG as negative control. Expression of CXCL16 on isolated monocytes was detected using allophycocyanin conjugated monoclonal anti-human CXCL16 (R&D Systems).…”
Section: Analysis Of Cxcl16 and Cxcr6 Cell Surface Expression Using Fmentioning
confidence: 99%
See 1 more Smart Citation
“…This model was based on investigations of chemokine interactions with chimeric receptors of CXCR1:3 (Xanthou et al, 2003) and CCR1:3 (Pease et al, 1998). Also supporting this, CX 3 CL1 depends on residues in the N terminus as well as ECL-3 of CX 3 C chemokine receptor 1 (Chen et al, 2006), and CXCL16 depends on all extracellular regions of CXCR6 (Petit et al, 2008). Likewise, we and others have reported that the chemokineinduced activation is critically dependent upon the receptor N terminus in CCR1, CCR2, and CCR8 (Samson et al, 1997;Jensen et al, 2008Jensen et al, , 2012.…”
Section: Role Of Disulfide Bridges In Homologous Chemokinementioning
confidence: 78%